(untitled) (Atlas Journal of Biology, 2017)
The 2,4,6-trinitrotoluene (TNT), 2,4-dinitrotoluene (2,4-DNT), and Toluene derived from a nitroaromatic compound(NAC) cause high toxicity and mutagenicity to environment. One of best methods to remove their toxicity from contaminated soil is known biological remediation with soil bacteria. Total of 235 strains of explosives-removing soil bacteria were isolated from the shooting gallery at a military base in Korea. They were identified as Acinetobacter, Agrobacterium, Alcaligenes, Flavobacterium, Klebsiella, Pseudomonas, Serratia, and Citrobacter species. After further screened for the better removal efficiencies, KT22 identified as Serratia sp., KD4 identified as Klebsiella sp., and KD6 identified also as Klebsiella sp. showed the highest removal efficiency for TNT, 2,4-DNT, and 2,6-DNT, respectively. The optimal removal conditions were shown as follows: cell concentration 1 g/L, pH 7, and temperature 25-30°C. In a Luria-Bertani (LB) medium containing 100 mg/L of TNT, KT22 strain could remove TNT over 99% and showed a good biomass growth after 6 h of incubation. Furthermore, when the KT22 strain was mixed with a Bacillus sp., the mixed culture showed the improved TNT removal efficiency. Conclusively, this new strain could be most effective to remove NAC toxicity with rhizosphere remediation system on contaminated soil.